Deubiquitinase Ubiquitin‐Specific Protease 29 Ameliorates Pathological Cardiac Hypertrophy through Inhibiting Transforming Growth Factor β‐Activated Kinase 1 - Xi Jiang; Yan Sun; Hongjie Shi; Zhen Liu; Jianqing Zhang; Changlu Xu; Yufeng Hu; Tiesheng Niu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Pathological cardiac hypertrophy, characterized by the involvement of multiple regulators, ultimately leads to heart failure in the absence of effective interventions. The identification of key factors involved is crucial for exploring novel treatments for heart failure. However, the function and pathological implications of USP29 (ubiquitin‐specific protease 29) in cardiomyocytes remain unknown. Methods and Results The impacts of USP29 on pathological cardiac hypertrophy were investigated through the use of knockout/overexpression mice and overexpression/knockdown cardiomyocytes, accompanied by bioinformatic analysis and multiple molecular biological techniques to elucidate the underlying mechanisms. We observed upregulation of USP29 protein levels in both transverse aortic constriction‐induced hypertrophic hearts (upregulated by 159.8%) and phenylephrine‐induced hypertrophic cardiomyocytes (upregulated by 184.6%). Moreover, genetic knockout of USP29 in mice exacerbated transverse aortic constriction‐induced heart hypertrophy, dysfunction, and fibrosis, whereas overexpression of USP29 in cardiomyocytes using adeno‐associated virus 9 effectively attenuated the hypertrophic response. Similarly, USP29 alleviated phenylephrine‐induced hypertrophy of primary neonatal rat cardiomyocytes. Mechanistically, the cardioprotective effects mediated by USP29 were attributed to its suppression of TAK1 (transforming growth factor β‐activated kinase 1) activation. Further molecular analysis revealed that USP29 directly interacts with TAK1 through amino acids 284 to 922 of USP29 and amino acids 1 to 306 of TAK1, subsequently inhibiting TAK1 activation via K63‐linked deubiquitination, which is indispensable for regulating cardiac hypertrophy by USP29. Conclusions Here, we have identified USP29 as a novel negative regulator of pathological cardiac hypertrophy. Our findings suggest that targeting either USP29 or its interaction with TAK1 could represent an innovative therapeutic strategy for treating heart failure and cardiac hypertrophy.